An Eco-Technological Approach to Handcraft Production. Two Cases in the Colombian Caribbean Region - Pacheco, Juan Carlos (2013)
The present article is a result of the research entitled “An eco-technological model for handicraft production in wood carving and weaving with Iraca fibres” with the rural communities of Galapa and Usiacurí, located in the Colombian Caribbean region. We centered our analysis on the productive reality of the artisan communities, for which we sought the relations between the variables associated to the local technology. We worked using participatory methodologies. The eco-technological model we obtained reveals the complexity of the key relations existing among the artisan groups in order to achieve an appropriate productivity level. We concluded that the global economic challenges for the rural artisans calls for a technological productivity based on the sustainable use of the natural resources that is necessary for the handcraft production.